Majesty of Limbu Love Songs: The Case of Sambahamphe's Char Maya Palam - Limbu, Ramesh Kumar (JODEM: Journal of Language and Literature, 2021)
Folklore studies, also known as folkloristics, studies customs, traditions, artifacts and beliefs being transmitted from past generations to the present. Transmission of these artifacts is a vital part of the folklore process. This article examines how Limbu love song, known as palam, splendidly characterizes the multiple aspects of love functioning as a sense of propriety and decorum. Palam is a popular folksong in Yakthung Limbu community of Nepal. It is also sung in many other countries of the world where Limbu community populate including India, Bhutan and Myanmar. Focusing on the text Char Maya Palam by Ambika Kumar Sambahamphe, the study attempts to analyse how the palam or Limbu love song, which is sung while dancing ya?lang, undeniably holds substantial popularity and esteemed value in Limbu traditional folksongs.